A Course in Academic Writing as a Vehicle for Personal Growth and Transformation. (3rd July 2022) - Alston, Christina; Mirghassemi, Fatemeh; Gist, Conra D.
Abstract : Scholarly writing is traditionally written and reviewed with a positivist mindset, based on ideas of universal truths that typically remove subjectivisms, cultural experiences, and marginalized voices from the writing process. Writing in this manner fails to recognize how the societal and internalized ideas of white dominance can negatively influence how Black, Indigenous, and People of Color (BIPOC) understand academic writing. Challenging this limited view of academic writing is essential; otherwise, rising BIPOC scholars may learn to withhold their voices and lived experiences from their writing. Pedagogical approaches that equip emerging BIPOC scholars to find and cultivate their academic writing identities are vital to nurturing their sense of agency. This article explores what these approaches may look like by centering the experiences of two BIPOC graduate students in an academic writing class and reflecting on their evolution as scholarly writers. Characteristics of the course are critically analyzed to identify how the reflective component of the course contributed to these students' perceptions of what scholarship entails and how valuable their contributions are to academia. Students also shared how their changed perceptions of academic writing allowed them to overcome fears and contribute successfully to their field's publications.